2017
DOI: 10.1155/2017/4651518
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Fractures in the Elderly: Midterm Outcomes of Column Stabilisation and Primary Arthroplasty

Abstract: Background. Interest in arthroplasty techniques for periarticular or intra-articular fractures in the elderly/osteoporotic patient continues to rise, including for geriatric acetabular fractures. In line with this, many acetabular fracture surgeons are now undertaking acute total hip arthroplasty in elderly/osteoporotic patients. Little is known however of the outcomes of this procedure, beyond the first year after surgery. Questions/Purposes. We determined the clinical outcomes of a series of elderly osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…We obtained the full-text of all potentially relevant reports and two review authors (EL, HP) independently screened all full-text reports for inclusion and exclusion criteria. Twenty-five articles were excluded after full text review for the following reasons: seven non-English language articles, 10 , 11 , 12 , 13 , 14 , 15 , 16 eight articles describing acute fracture management or lacking delayed THA, 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 eight articles with insufficient sample size (case reports and review articles), 5 , 6 , 25 , 26 , 27 , 28 , 29 , 30 one article with insufficient outcome data or follow-up duration, 31 and one article with co-occurring femur fractures and other ipsilateral injuries. 32 Cases of disagreement were resolved by discussion, and if no consensus was reached a third review author (SN) was consulted to make the decision.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained the full-text of all potentially relevant reports and two review authors (EL, HP) independently screened all full-text reports for inclusion and exclusion criteria. Twenty-five articles were excluded after full text review for the following reasons: seven non-English language articles, 10 , 11 , 12 , 13 , 14 , 15 , 16 eight articles describing acute fracture management or lacking delayed THA, 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 eight articles with insufficient sample size (case reports and review articles), 5 , 6 , 25 , 26 , 27 , 28 , 29 , 30 one article with insufficient outcome data or follow-up duration, 31 and one article with co-occurring femur fractures and other ipsilateral injuries. 32 Cases of disagreement were resolved by discussion, and if no consensus was reached a third review author (SN) was consulted to make the decision.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have referenced the paucity of information on HE skeletal trauma in the elderly. 8,10,11 Indeed, a recent review highlighted the lack of information on this increasingly important injury. 1,12…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, another analysis of 24 elderly osteoporotic patients treated for acetabular fracture were evaluated for clinical outcomes, with a mean follow up period of 49 months after surgery. The results of the study showed no complication after the perioperative period, the mean Harris Hip Score was noted as 92 & no acetabular components were loose on latest radiographs or clinically, 13 of 14 hips rated as good or excellent 21 . A study conducted at Sanjay Gandhi Institute of Trauma and Orthopaedics.…”
Section: Discussionmentioning
confidence: 77%